Clinical features and outcomes of COVID-19 patients previously vaccinated with COVID vaccine - Maddimani, Ramesh S.; Krishnegowda, Ravi; Yadav, Kushal; Janaki, Aishwarya; Subramanya, Sachin (International Journal of Advances in Medicine, 2023)
Background: With countries facing multiple waves of COVID-19 disease throughout the world it is the need of the hour to vaccinate individuals to protect against the deadly virus. Vaccination has shown noteworthy results with reduction in cases, however despite of vaccination many individuals have been infected with SARS-CoV-2 virus. Aims and objectives were to compare the outcomes of COVID-19 positive individuals who have previously received at least one dose of COVID-19 vaccine with unvaccinated individuals and to study the demographic and clinical features in COVID-19 patients who have previously received at least one dose of COVID-19 vaccine. Methods: This prospective, observational single-center study considered adults patients from April to May 2021 who were diagnosed with COVID 19 infection by RT-PCR technique or Rapid Antigen Test. The sample size for the study was 3076, out of which 2969 were unvaccinated and 107 were vaccinated. Necessary clinical data were collected and selected subjects were followed up until discharge or death. Statistical analysis was carried out using SPSS version 24. Results: Out of 3076 patients, 2002 (65.08%) were males and 1074 (34.92%) were females. There were 2969 individuals (96.52 %) who were unvaccinated and 107 (3.48 %) individuals who had received at least one dose any of the COVID 19 vaccines. Among the unvaccinated individuals, 895 (30.1%) succumbed to death and 2074 (69.9%) were discharged. Among the vaccinated individuals 19 (17.8%) succumbed to death and 88 (82.2%) were discharged (Odds ratio-0.5002) (CI-0.3029 to 0.8265). Conclusions: Vaccination decreases the severity and mortality of the disease. Genetic variants might have a key role and further studies regarding the variants of SARS-CoV-2 is needed.